Social Autopsy is a dire need for investigating child mortality in Pakistan - Siddiqui, Muhammad Bilal; Wan Ng, Chiu; Wah Yun Low (International Journal of Endorsing Health Science Research, 2016)
The world has been unable to meet the United Nations Millennium Development Goals (MDGs) of reducing child mortality by 2015. Since 1990, there is an established disparity of under-5 mortality rates among countries across the globe. This disparity is due to high burden of child deaths in several of the low income countries. These high burden countries includes India, Nigeria, Pakistan and Democratic Republic of the Congo (DRoC) (UNICEF-Report-2015). Currently, these four countries carry almost 45% of the global burden of child deaths. If these high burden countries continues to shows such trends of child mortality, then in the next 15 years or so, they will be carrying almost half of the global burden of child mortality (UNIGCME-2015).